Cost-efficient microbial electrosynthesis of hydrogen peroxide on a facile-prepared floating electrode by entrapping oxygen. (December 2021) - Wang, Guan; Yao, Yuechao; Tang, Kai; Wang, Guochen; Zhang, Wenjing; Zhang, Yifeng; Rasmus Andersen, Henrik
Graphical abstract: Highlights: A high H2 O2 generation rate was achieved without aeration, using a floating cathode. COD usage and current efficiency were enhanced compared to a commercial GDE. Energy and chemicals use reduced compared to established (bio-)electrode methods. Traditional two-step calcined electrode preparation method was reduced to one step. Integrated H2 O2 synthesis with neutral Fenton treatment for micro-pollutant removal. Abstract: Microbial electrosynthesis of hydrogen peroxide is receiving growing interest for a green substitute for anthraquinone process. However, poor oxygen transmission of electrode remains an obstacle to enhance H2 O2 production rate without aeration. Here, a superhydrophobic natural air diffusion floating electrode (NADFE), which naturally and efficiently entraps O2 in the air, was proposed for the first time to improve microbial electrosynthesis of H2 O2 . Furthermore, a one-step calcined electrode preparation method was developed to reduce energy consumption further. In the microbial electrolysis cell with the NADFE, a high H2 O2 production rate of 39 mg/L/h and current efficiency of 86% were achieved without aeration. The production rate of H2 O2 was 2.2 times that of a gas diffusion electrode. Importantly, the energy consumption was 34.3 times lower than an electrochemical system. Therefore, the high H2 O2 production rate and current efficiency, and low energy consumption of the process provide a superior alternative for environmental remediation.